2022
DOI: 10.1111/jipb.13210
|View full text |Cite
|
Sign up to set email alerts
|

Shaping polyploid wheat for success: Origins, domestication, and the genetic improvement of agronomic traits

Abstract: Bread wheat (Triticum aestivum L., AABBDD, 2n = 6x = 42), which accounts for most of the cultivated wheat crop worldwide, is a typical allohexaploid with a genome derived from three diploid wild ancestors. Bread wheat arose and evolved via two sequential allopolyploidization events and was further polished through multiple steps of domestication. Today, cultivated allohexaploid bread wheat has numerous advantageous traits, including adaptive plasticity, favorable yield traits, and extended end-use quality, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 291 publications
(404 reference statements)
0
15
0
Order By: Relevance
“…Polyploid hybridization between tetraploid and diploid wheat gave rise to the allohexaploid wheat, which has become one of the major crops contributing to its genome plasticity ( Dubcovsky and Dvorak, 2007 ; Liu et al, 2021 ). Since numerous desirable agronomic characteristics are contained in tetraploid wheat, many research focused on the introgression of beneficial genes and traits into hexaploid wheat ( Xie and Nevo, 2008 ; Nevo et al, 2013 ; Peng et al, 2013 ; Nevo, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyploid hybridization between tetraploid and diploid wheat gave rise to the allohexaploid wheat, which has become one of the major crops contributing to its genome plasticity ( Dubcovsky and Dvorak, 2007 ; Liu et al, 2021 ). Since numerous desirable agronomic characteristics are contained in tetraploid wheat, many research focused on the introgression of beneficial genes and traits into hexaploid wheat ( Xie and Nevo, 2008 ; Nevo et al, 2013 ; Peng et al, 2013 ; Nevo, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, the TaBOR3 subfamily contains eight members, indicating an expanded number of members. Both wheat and rape were polyploidy crops that occurred through genome duplication events, which may be the reason for the copy number expansion of the BOR gene in wheat and in the B. napus genome, enhancing the adaptability of crops to different environments ( Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Common wheat ( Triticum aestivum L.) is one of the most important food crops, with a large and complex genome that has undergone two rounds of polyploidization (Liu et al ., 2022). Multiple studies showed that the complexity of gene regulation in wheat involves coordinating both transcriptional and epigenetic regulations among subgenomes.…”
Section: Introductionmentioning
confidence: 99%